PENGARUH STRATEGI PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Etin Solihatin (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2011)
ABSTRACT With regards to findings of the study, it can be concluded that in general, (1) the use of Cooperative Learning strategy has given higher achievement in learning Civics than that of Expository one; (2) the use of Cooperative Learning strategy with learners of field independent learning style has effect in the form of higher achievement in learning Civics than that of Expository one; (3) the use of Cooperative Learning strategy with learners of field dependent learning style has effect in the form of lower achievement in learning Civics than that of Expository one; and (4) there is interaction between the use of learning strategy and learner's learning style on learner's achievement in learning Civics.